2017
DOI: 10.28945/3893
|View full text |Cite
|
Sign up to set email alerts
|

Students Learning to Program by Developing Games: Results of a Year-long Project in Primary School Settings

Abstract: Aim/PurposeThe purpose of this study was to examine whether the authoring of computer games in a mainstream primary school setting can support the learning of game design and programming concepts. Background Despite the benefits for students when they learn how to program and the significant body of research regarding this matter, these benefits are still under debate, and the teaching of programming has a relatively undeveloped pedagogy. With this in mind, a project was designed and implemented, having constr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
6

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 64 publications
1
6
0
6
Order By: Relevance
“…Yet, in line with previous studies (e.g., Chang et al, 2019;Huang et al, 2019;Lee et al, 2017), we found that students were more motivated to learn than in conventional teaching and had a more enjoyable learning experience. Consequently, motivation offers a plausible explanation for our results, as it directly (and positively) affects the learning outcomes in almost all teaching subjects (Fokides, 2017;Fokides & Atsikpasi, 2018). The same applies for enjoyment; it is as a rather common finding in most research regarding the educational uses of 360 o videos, positively correlated (together with motivation) with the learning outcomes (e.g., Chang et al, 2019;Huang et al, 2019;Rasheed et al, 2015).…”
Section: Discussionsupporting
confidence: 56%
“…Yet, in line with previous studies (e.g., Chang et al, 2019;Huang et al, 2019;Lee et al, 2017), we found that students were more motivated to learn than in conventional teaching and had a more enjoyable learning experience. Consequently, motivation offers a plausible explanation for our results, as it directly (and positively) affects the learning outcomes in almost all teaching subjects (Fokides, 2017;Fokides & Atsikpasi, 2018). The same applies for enjoyment; it is as a rather common finding in most research regarding the educational uses of 360 o videos, positively correlated (together with motivation) with the learning outcomes (e.g., Chang et al, 2019;Huang et al, 2019;Rasheed et al, 2015).…”
Section: Discussionsupporting
confidence: 56%
“…When the methods used by teachers are examined in the literature, it is seen that the demonstration method is used frequently (Akbıyık & Seferoğlu, 2012). Additionally, it is seen that teaching by giving game programming tasks to students is beneficial (Fokides, 2017;Jenson & Droumeva, 2016;Nouri, Norén, & Skog, 2018). In addition, teaching methods such as digital story writing (Hansen et al, 2016) and mobile application development (John & Rani, 2015) are seen to be applied.…”
Section: Discussionmentioning
confidence: 99%
“…Birçok alanın öğretiminde olduğu gibi bilgisayar bilimleri eğitimi ve kodlama öğretiminde de farklı yaklaşımlar uygulanmaktadır. Alanyazında, bilgisayar bilimleri eğitiminde oyun programlama yaklaşımının sıklıkla denendiği (Fokides, 2017;Jenson ve Droumeva, 2016), araç kitleriyle öğretimin yapıldığı (Arabacıoğlu, Bülbül ve Filiz, 2007;Raab, Rasala ve Proulx, 2000), öğrencilerin öğrenme nesneleri tasarladığı (Abad, 2008), dijital hikâye yazdığı (Hansen ve diğ., 2016), mobil uygulama geliştirdiği (John ve Rani, 2015) çalışmalar görülmektedir. Ayrıca robot programlama (Ersoy, Madran ve Gülbahar 2011), e-öğrenme ortamında probleme dayalı öğrenme (Bashir ve Hoque, 2016), Alice programlama aracının kullanımı ve nörodidaktik yöntemler (Sabitzer, 2011) önerilen yaklaşımlar olarak karşımıza çıkmaktadır.…”
Section: Kodlama öğRetimi Ve Araçlarunclassified
See 2 more Smart Citations